KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH KABUPATEN SITUBONDO - Riska Dwi Fitriana; Nur Hidayati; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine how much influence the clarity of budget targets,accounting controls, and reporting systems on the accountability of theperformance of Situbondo District government agencies. The data used in thisstudy is primary data, the sample in this study is the SKPD and the head of thevillage government in Situbondo Regency. The sampling technique was carriedout using purposive sampling method. The results obtained using multiple linearregression test Y = 3,576 + 0,086 X1 + 0,193 X2 + 0,805 X3 and the test fromthis study using t test. The results of this study indicate that partially the BudgetTarget Clarity variable does not affect the Performance Accountability ofGovernment Agencies. While the Accounting Control variables and reportingsystem have a positive effect on the Performance Accountability of GovernmentAgencies.Keywords: Budget Target Clarity, Accounting Control and reporting system